A CRISPR-Cas12a-based platform for ultrasensitive rapid highly specific detection of Mycobacterium tuberculosis in clinical application - Jia, Nan; Wang, Chaohong; Liu, Xiaming; Huang, Xiaolan; Xiao, Fei; Fu, Jin; Sun, Chunrong; Xu, Zheng; Wang, Guirong; Zhou, Juan; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Tuberculosis, caused by Mycobacterium tuberculosis (MTB), is the second leading cause of death after COVID-19 pandemic. Here, we coupled multiple cross displacement amplification (MCDA) technique with CRISPR-Cas12a-based biosensing system to design a novel detection platform for tuberculosis diagnosis, termed MTB-MCDA-CRISPR. MTB-MCDA-CRISPR pre-amplified the specific sdaA gene of MTB by MCDA, and the MCDA results were then decoded by CRISPR-Cas12a-based detection, resulting in simple visual fluorescent signal readouts. A set of standard MCDA primers, an engineered CP1 primer, a quenched fluorescent ssDNA reporter, and a gRNA were designed targeting the sdaA gene of MTB. The optimal temperature for MCDA pre-amplification is 67°C. The whole experiment process can be completed within one hour, including sputum rapid genomic DNA extraction (15 minutes), MCDA reaction (40 minutes), and CRISPR-Cas12a-gRNA biosensing process (5 minutes). The limit of detection (LoD) of the MTB-MCDA-CRISPR assay is 40 fg per reaction. The MTB-MCDA-CRISPR assay does not cross reaction with non-tuberculosis mycobacterium (NTM) strains and other species, validating its specificity. The clinical performance of MTB-MCDA-CRISPR assay was higher than that of the sputum smear microscopy test and comparable to that of Xpert method. In summary, the MTB-MCDA-CRISPR assay is a promising and effective tool for tuberculosis infection diagnosis, surveillance and prevention, especially for point-of-care (POC) test and field deployment in source-limited regions.